Flexible laryngeal mask with pharyngeal suction for nasal surgery. (June 2019) - Zhou, Gary X.; Rosenblatt, William; Zhou, Sonya E.; Dai, Feng; Heerdt, Paul M.
Abstract: Method: Peri-operative data of 71 healthy patients who underwent nasal surgery using flexible laryngeal mask attached with two pharyngeal suction catheters were retrospectively analyzed to examine the evidence of glottic contamination and to assess the relationship between postoperative sore throat and the pharyngeal suction. Results: No patient experienced hypoxemia or laryngospasm during the surgery and emergence. Visually, examination showed no evidence of blood contamination on the laryngeal surface of the laryngeal mask. The amount of blood evacuated from the pharynx through the attached catheters correlated with the amount of estimated blood loss and the duration of surgery (rho = 0.82 and 0.51, respectively; P < 0.001). The incidence of postoperative sore throat (19.3%) was similar to that reported in the literature, while the duration of surgery and the amount of blood evacuated from the pharynx were not different between patients with and without sore throat ( P = 0.98 and 0.70, respectively). Conclusions: The flexible laryngeal mask with pharyngeal suction catheters provided safe airway management for nasal surgeries without apparent glottic contamination or other airway-related complications and was not associated with an increased risk of postoperative sore throat in this retrospective observational study. A large controlled prospective study is needed to confirm these findings. Highlights: Suction catheters affixed to LMA remove pharyngeal blood during nasal surgery. No evidence of airway contamination with blood using this method. No increased incidence of postoperative sore throat with this method.